Potensi Si Wuwu Areng Gethak (seni wayang bayang wuluhan dan tarian topeng gethak) sebagai media pencegahan untuk menghentikan stigma terhadap disabilitas remaja dan kusta berdasarkan kearifan lokal Pandalungan: Potential of Si Wuwu Areng Gethak (wuluhan shadow puppet art and gethak mask dance) as a preventive media to stop the stigma of adolescent disabilities and leprosy based on Pandalungan local wisdom - Hidayaturrohkim, Riski (Widya Kesehatan, 2024)
Disability is defined as the result of the interaction of individual limitations with their environment, not only physically and mentally but impacting activity limitations and barriers to participation. The purpose of writing is to find out the potential of the Si Wuwu Areng Gethak program as a preventive medium to stop the stigma of youth with disabilities and leprosy based on Pandalungan local wisdom. The writing method uses a literature review through electronic database literature and then synthesis is carried out according to the purpose of writing. adolescents with disabilities are more prone to experiencing cases of bullying by their peers, while those with leprosy have difficulties accessing health services because of shame and social isolation. The idea of the Si Wuwu Areng Gethak program is the utilization of Pandalungan Madura art as a preventive medium to stop the stigma of persons with disabilities, youth, and leprosy. The results of the SWOT analysis show that the percentage of driving force of 74.13% is sub-conducive to implementation. It is hoped that the idea of this program can be implemented through collaboration between academics and cross-sectoral synergy in education and health promotion